2010
DOI: 10.1021/nl904082k
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Triazine Framework as Catalytic Support for Liquid Phase Reaction

Abstract: An important goal in the preparation of highly active supported metal particles is the enhancement of the metal support interaction, providing a more stable catalyst, especially for liquid phase reactions as the leaching and reconstruction of the active phase causes deactivation. In this work, a covalent triazine framework (CTF) as support for Pd nanoparticles is compared to activated carbon (AC), the typical support used in liquid phase reactions. The results indicate that the presence of the N-heterocyclic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
257
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 372 publications
(269 citation statements)
references
References 35 publications
(64 reference statements)
2
257
0
7
Order By: Relevance
“…Among the various dopants, nitrogen attracted most interest [15,[20][21][22]. and applications of transition metal/N-doped graphene (NGr) based catalytic systems ranges from oxygen reduction reactions (ORR) [23][24][25][26], hydrogen evolving reactions (HER) [27,28], photocatalysis [29,30], oxidation [31][32][33][34][35][36][37][38], and reduction [39][40][41][42][43][44] reactions of organic molecules, C-C bond formation [45] to many others [46][47][48][49][50][51]. Hence, merging rationally-designed suitable modified supports with cheap transition metals permits access to the design of active, selective and cheap catalytic materials thus allowing to match or to outperform noble-metal-based catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various dopants, nitrogen attracted most interest [15,[20][21][22]. and applications of transition metal/N-doped graphene (NGr) based catalytic systems ranges from oxygen reduction reactions (ORR) [23][24][25][26], hydrogen evolving reactions (HER) [27,28], photocatalysis [29,30], oxidation [31][32][33][34][35][36][37][38], and reduction [39][40][41][42][43][44] reactions of organic molecules, C-C bond formation [45] to many others [46][47][48][49][50][51]. Hence, merging rationally-designed suitable modified supports with cheap transition metals permits access to the design of active, selective and cheap catalytic materials thus allowing to match or to outperform noble-metal-based catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…This trend can be explained by observing the AuPd particle sizes (4.5, 4.1 and 3.5 nm, for Au6Pd4 supported on CNFs, TiO2 and CNTs, respectively). Indeed, it has been reported that the metal nanoparticle size is one of the factors influencing the selectivity in glycerol oxidation, with larger particles giving higher selectivity towards glyceric acid [8][9][10][11][12][13][14][15]. Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…The heterocycles containing s-triazines in the nucleus had en successfully tested against various microes and it was found that they possess potential therapeutical value [11] for several diseases. So these compounds possess their own importance in medical faculty, pharmaceutical, industrial and agricultural field.…”
Section: Introductionmentioning
confidence: 99%
“…So these compounds possess their own importance in medical faculty, pharmaceutical, industrial and agricultural field. Some triazines contain anticancer [5], antitumor [12], antidiabtic [5,6] and anti-inflammatory [10][11][12] properties.…”
Section: Introductionmentioning
confidence: 99%